Los españoles y las vías de comunicación entre los diversos pueblos de Pangasinán, Filipinas - Albarrán González, Benigno (Estudios humanísticos. Geografía, historia y arte, 1992)
As towns came into being in Pangasinan, the Spaniards saw to it that proper communications be established. In order to link them, roads, pathways, bridges, and so on, were built by the natives under the supervision of the Spanish missionaries.